The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/hbm.21347
|View full text |Cite
|
Sign up to set email alerts
|

The role of the anterior cingulate cortex in emotional response inhibition

Abstract: Although the involvement of the anterior cingulate cortex (ACC) in emotional response inhibition is well established, there are several outstanding issues about the nature of this involvement that are not well understood. The present study aimed to examine the precise contribution of the ACC to emotion-modulated response inhibition by capitalizing on fine temporal resolution of the event-related potentials (ERPs) and the recent advances in source localization. To this end, participants (N = 30) performed an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 76 publications
11
106
1
Order By: Relevance
“…Collectively, these studies suggest that conflict monitoring processes are not sensitive to emotion. Also consistent with other studies, we observed that Nogo-P3 was enhanced in the presence of positive emotional stimuli [44,45]. The most common interpretation of emotional potentiation of the P3 is that sustained attentional engagement with positive emotional stimuli affects the execution or evaluation of inhibitory processing.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Collectively, these studies suggest that conflict monitoring processes are not sensitive to emotion. Also consistent with other studies, we observed that Nogo-P3 was enhanced in the presence of positive emotional stimuli [44,45]. The most common interpretation of emotional potentiation of the P3 is that sustained attentional engagement with positive emotional stimuli affects the execution or evaluation of inhibitory processing.…”
Section: Discussionsupporting
confidence: 92%
“…Behaviourally, emotional stimuli were associated with marginally better performance on Nogo trials, consistent with a "freezing" effect of emotion, perhaps driven by attentional prioritisation of emotional stimulus processing [50]. Turning to the ERP measures, we found no effect of emotion on the Nogo-N2, consistent with other studies [44,45]. Collectively, these studies suggest that conflict monitoring processes are not sensitive to emotion.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations